A Creditable Performance under the Circumstances? Suematsu Kenchô and the Pre-Waley Tale of Genji - Henitiuk, Valerie (TTR, 2010)
Before Suematsu’s 1882 translation of the Tale of Genji, the information available in the West about Murasaki Shikibu’s masterpiece was sketchy and erroneous. The main objectives of this translator were to improve Japan’s political status by demonstrating that it has a rich literary tradition, and to make known to Westerners what is in effect that nation’s “cultural scripture” (Rowley). Reaction to his version was conflicted: readers and reviewers are curious about the previously unsuspected literary wealth presented to them, but struggle to comprehend and find points of reference. My article focuses on the circumstances that made possible this early representation of Japanese literature, while paradoxically keeping the Genji from being widely read and admired until Waley’s famous translation appeared some 40 years later. I argue that Suematsu, in using this book to critique Anglo-American imperialism, nonetheless reveals his own ambivalent relationship with the text and its author. Further, Western audiences were ill-equipped to judge what they were reading, as well as reluctant to accept a non-European interpreter, and thus the reception of this world masterpiece was long stalled for reasons that had little to do with literary or translation quality.